FAKTOR DETERMINAN SOSIAL YANG MEMPENGARUHI KEGAGALAN PEMBERIAN ASI EKSKLUSIF DI SRATUREJO, BAURENO, KOTA BOJONEGORO - Ramadhani, Febriyanti (Jurnal Ilmu Kesehatan Masyarakat, 2019)
The breast milk is the best food for babies right for infancy up to 6 months. Breast milk not only benefits the baby, but also brought benefits the mother. Globally, only 38% of infants aged 0 - 6 months are exclusively breastfed. The latest analysis of non-exclusive breastfeeding contributes to 11.6% of deaths in children under 5 years of age. This is equivalent to around 804,000 child deaths in 2011 (WHO, 2012). This research was conducted to analyze the social determinant factors that affect the failure of Exclusive Breast Feeding in Sraturejo, Baureno , Bojonegoro City. This research was an observational analytic study with a quantitative approach. The research was a cross sectional design. The research was conducted in Sraturejo Village, Baureno, Bojonegoro from 3 July to 9 August 2018. The population were 150 mothers who had children aged 0-24 months. The sample is calculated using the simple random sampling formula which resulted to 110 mothers who have babies 0-24 months of age. The data collection technique used primary data, by filling out the questionnaires of knowledges, attitudes, and behaviors. Then the priority of the problem will be determined using the USG matrix, which the proceeded with finding the cause of the problem with the metaplan technique and a fishbone diagram to identify the root causes of a problem. Then the analysis is conducted with the SWOT method. The results showed no corelation between knowledge and behavior, and there was no corelation between attitude and behavior. Other social determinants discovered are information, methods, economics, environment, individuals, and health. The social determinant factors that most affected the failure of exclusive breastfeeding are economic factors, such as working mothers. The conclusion is that working mothers affected the failure of exclusive breastfeeding.